Effect of VIPS fabrication parameters on the removal of acetic acid by supported liquid membrane using a PES-graphene membrane support - Norlisa, Harruddin; Syed Mohd Saufi, Tuan Chik; C. K. M., Faizal; Abdul Wahab, Mohammad (Royal Society of Chemistry, 2018)
In this study, the removal of acetic acid by supported liquid membrane (SLM) using hybrid polyethersulfone (PES)–graphene membrane prepared by vapor induced phase separation (VIPS) was investigated. The effects of graphene loading, coagulation bath temperature, air exposure time, and air humidity on the morphology, mechanical strength, porosity, and contact angle of the membrane were analyzed. The performance and stability of the hybrid membrane as a SLM support for acetic acid removal were studied. The best PES–graphene membrane support was produced at a coagulation bath temperature of 50 °C, an air exposure time of 30 s and air humidity of 80%. The fabricated membrane has a symmetrical micropore cellular structure, high porosity and high contact angle. Under specific SLM conditions, almost 95% of acetic acid was successfully removed from 10 g L−1 aqueous acetic acid solution. The hybrid membrane remains stable for more than 116 h without suffering any membrane breakage during the continuous SLM process.